2021
DOI: 10.22219/jrak.v11i2.17400
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Risk, Trust, Social Influence On ZIS Online Payment Adoption: Generation-Z Perspectives

Abstract: Technological developments encourage people to make changes in their lives. The emergence of various kinds of online payment systems has made human life easier in completing various transaction activities. With online payment technology, ZIS payment activities can be done cashless. The respondents in this study were Generation Z. This research’s testing is using SMART PLS 3.0. Generation Z has several factors that are considered to be intense in using ZIS online Payment. To be able to continue to be intense, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
(56 reference statements)
0
7
2
1
Order By: Relevance
“…Peningkatan layanan e-commerce oleh perusahaan penyedia layanan merupakan salah satu bentuk untuk mempengaruhi pengguna melalui kepercayaan atas e-commerce (Mohammed & AlShahri, 2021). Pada dasarnya kepercayaan didorong oleh faktor Risiko, Kegunaan, Kemudahan Penggunaan, dan Pengaruh Sosial, Sehingga kepercayaan dapat meningkatkan jumlah pembelian melalui e-commerce (Oktavendi, & Mua'ammal 2021;Tampubolon & Sharif, 2022), sehingga penjualan melalui e-commerce akan dijadikan sebagai strategi pelaku UMKM dalam menjalankan usahanya dengan adanya kepercayaan. Hipotesis keempat menyatakan bahwa interaktivitas berpengaruh terhadap penggunaan e-commerce.…”
Section: Uji Hipotesisunclassified
“…Peningkatan layanan e-commerce oleh perusahaan penyedia layanan merupakan salah satu bentuk untuk mempengaruhi pengguna melalui kepercayaan atas e-commerce (Mohammed & AlShahri, 2021). Pada dasarnya kepercayaan didorong oleh faktor Risiko, Kegunaan, Kemudahan Penggunaan, dan Pengaruh Sosial, Sehingga kepercayaan dapat meningkatkan jumlah pembelian melalui e-commerce (Oktavendi, & Mua'ammal 2021;Tampubolon & Sharif, 2022), sehingga penjualan melalui e-commerce akan dijadikan sebagai strategi pelaku UMKM dalam menjalankan usahanya dengan adanya kepercayaan. Hipotesis keempat menyatakan bahwa interaktivitas berpengaruh terhadap penggunaan e-commerce.…”
Section: Uji Hipotesisunclassified
“…Several studies have shown that the effectiveness of distribution in donating that is felt by donors has a positive effect in this case with the use of technology, including those carried out by (Ninglasari & Muhammad, 2021) analyze the role of digitalization in the management of zakat during the Covid-19 pandemic, (Kusumawardani, 2020) examines the influence of the quality of public governance, accountability and effectiveness on the intention of members of the Yogyakarta Indonesian Chinese Islamic Association (PITI) in paying zakat, (Muhammad & Saad, 2016) regarding the quality, accountability and effectiveness of public governance on the intention to pay zakat, (Hudaefi & Beik, 2020) Learn about digital zakat campaign tools during the Covid-19 outbreak, (Cahyani et al, 2022), developing the UTAUT model by adding zakat knowledge as a moderating variable on interest in paying zakat using a digital platform, (Wang et al, 2019) found that perceived donor effectiveness has a positive effect on the intention to donate through crowdfunding, (Farooq et al, 2020) presents a blockchain-based charity management platform that aims to provide a safe, transparent and efficient system for donations, (Kashif et al, 2018) found that informants or zakat actors prefer to donate zakat directly, this is due to a lack of trust in zakat institutions, (Choi et al, 2019) examines the mediating effect of online donations on youth donation awareness, as well as the pathways of online donations to intention to donate again in the future, (Rahman & Idrus, 2022) analyze the factors that influence online zakat payments, (Maleki & Hosseini, 2020) analyze the factors that influence the intention to donate through mobile payment applications, (Wiharjo & Hendratmi, 2019) about interest in paying zakat, infaq and alms online in Kuala Lumpur, (Jamaludin et al, 2017) regarding the perception of the use of zakat, infaq and alms online in Indonesia, (Ichwan, 2020) regarding muzzaki's decision to pay zakat, infaq and alms through fintech gopay, (Amalia, 2018) regarding individual interest in using Paytren sharia fintech as a means of payment for donation transactions, (Niswah et al, 2019a) regarding the interest of the Muslim millennial community in donating using the fintech platform, (Usman, 2020) about the use of fintech in donating, (Oktavendi, 2021) regarding the adoption of online ZIS payments by Generation Z, (Arwanita, 2022) researching interest in paying ZIS through BSI Mobile, (Lathifah, 2020) which ...…”
Section: Rotated Component Matrixmentioning
confidence: 99%
“…Meanwhile, the opposite research in this study was carried out by (Sulaeman & Ninglasari, 2020) examines the determinants of the millennial generation's interest in paying zakat, infaq and alms online, (Astuti & Prijanto, 2021) who researched the interest in paying zakat through the kitabisa.com platform. Perceptions of the use of online zakat in Indonesia by (Wiharjo & Hendratmi, 2019); interest in using E-zakat in paying ZIS by (Kharisma & Jayanto, 2021); interest in using online zakat applications by (Purwanto et al, 2021) and interest in digital ZISWAF payments by (Hasyim et al, 2020); (Usman, 2020) regarding the use of fintech in donating, (Oktavendi, 2021) regarding the adoption of online ZIS payments by Generation Z; (Al-Athar, 2021) examines the millennial generation's intention to pay donations through digital payments; (Arwanita, 2022) researched the interest in paying ZIS through BSI Mobile; (Azizi, 2020) interest in using electronic money for ZIS payments to the people of the city of Semarang; (Sukoraharjo et al, 2018)analyzed the website of the amil zakat foundation on the intention to pay zakat online with the TAM approach; (Mohd Thas Thaker et al, 2018) regarding the interest in adopting the waqf crowdfunding model. (Yeubun, 2022) which examines the interest in paying zakat online in the people of Jayapura City.…”
Section: Rotated Component Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has increasingly increased the number of Fintech users (Fu & Mishra, 2022;Le, 2021) as consumers realize that Fintech services are very useful in today's life (Ambarsari et al, 2021;Le, 2021). In addition, Fintech is also able to answer the need by changing the supply chain networks in almost all business sectors Research on sustainable intentions to use Fintech is generally related to convenience, benefits, trustworthiness, risk, and security (Al Nawayseh, 2020;Ali et al, 2021;Daragmeh et al, 2021;Franque et al, 2021;Hasan et al, 2021;Jung et al, 2020;Le, 2021;Oktavendi, 2020;Oktavendi & Mu'ammal, 2021;Rabaai, 2021;Ryu, 2018;Sasongko et al, 2022;Setiawan et al, 2021;Setyaningsih et al, 2019;Shiau et al, 2020;Singh et al, 2020;Wang et al, 2019;Xie et al, 2021). Meanwhile, research on unsustainable intentions to use Fintech is undoubtedly related to the obstacles that arise from using information technology, in this case, Fintech.…”
Section: Introductionmentioning
confidence: 99%